Protestantism and education: Reading (the bible) and other skills - Timo Boppart; Josef Falkinger; Volker Grossmann (Center for Economic Studies and ifo Institute (CESifo), 2011)
During industrialization, Protestants were more literate than Catholics. This paper investigates whether this fact may be led back to the intrinsic motivation of Protestants to read the bible and whether other education motives were involved as well. We employ a historical data set from Switzerland which allows us to differentiate between different cognitive skills: reading, numeracy, essay writing and Swiss history. We develop an estimation strategy to examine whether the impact of religious denomination was particularly large with respect to reading capabilities. We find support for this hypothesis. However, Protestants' education motives went beyond reading the bible.
Keywords: I20; 330; cognitive skills; education; reading capability; religious denomination; protestant reformation; Bildungsverhalten; Protestantismus; Katholizismus; Vergleich; Schweiz